Mentoring Relationships and Experiences in Online Doctoral Education: Perceptions, Reality, and Action - Norina L. Columbaro; Catherine A. Hansman (Adult Education Research Conference, 2014)
This paper explores research and literature surrounding the existence and nature of mentoring relationships within online doctoral degree programs and how these relationships prepare online doctoral degree graduates for full-time, tenure track employment in higher education institutions.